Very low latitude (L = 1.08) whistlers - Singh, Rajesh; Cohen, Morris B.; Maurya, A.K.; Veenadhari, B.; Kumar, Sushil; Pant, P.; Said, Ryan K.; Inan, Umran S. (My University, 2012)
For decades, whistlers observed on the ground at mid and high latitudes have been used for diagnostics of Earth's plasmasphere. Whistlers have also been observed at low latitudes however, the propagation characteristics of low latitude whistlers are poorly understood thus they have not been used effectively as a diagnostic for the low latitude ionosphere. One key limitation with past studies has been lack of knowledge of the whistler source lightning location. Here we present the first cases of low latitude ground whistlers most likely linked with their causative lightning discharges in the conjugate zone. The Global Lightning Dataset 360 (GLD360) detected lightning discharges were found to be located close to the conjugate location of the recording stations, providing direct evidence of inter-hemispheric propagation at the low latitudes. A total of 864 whistlers were observed at Allahabad, India (Geomag. lat. 16.05°N; Geomag. long. 155.34°E; L = 1.08) during the night of 26 January 2011. Using GLD360 network data, we show the occurrence of thunderstorm activity between 200 and 450 km from the conjugate point of Allahabad. We also report the distribution of peak currents of whistler-producing lightning, which demonstrate a cutoff at 30 kA.
Keywords: Very low latitude; Plasmasphere; Global lightning dataset; Very low frequency